“No nation wanted it so much”: Beckett, Swift and Psychiatric Confinement in Ireland - Feargal Whelan (Estudios Irlandeses, 2019)
Samuel Beckett displays an interest in portraying figures normally regarded as insane within their communities, and who are frequently depicted interacting with institutions of mental care. Taking the representation of three asylums in three separate works, this paper aims to explore a developing and complicated meditation on the subjects of mental health and incarceration by the author. Beckett’s recurring reference to Jonathan Swift and the constant presence of sexual anxiety in these narratives allows him to produce a nuanced critique of the development of modes of confinement in the emerging Irish state.